Percepção ambiental e uso de plantas por moradores da zona de amortecimento do Parque Nacional de Sete Cidades, Piauí - Correia, Maria Luíza Dias (2020)
The use of natural resources has increased considerably in recent years, generating negative impacts and, thus, emphasizing the need for the development of studies that contribute to the elaboration of conservationist actions. It is in this perspective that the present research had as main objective to know the environmental perception and the use of the vegetal resources by inhabitants of the communities located in the buffer area of the Parque Nacional de Sete Cidades (PNSC), Piauí, that have been achieved through the lifting of the initial socio-economic profile of the communities; registration of the use of plants by residents of the buffer area of the Parque Nacional de Sete Cidades, Piauí; identification of the plant parts used and the form of use; diagnosis of the environmental perception that local residents have in relation to the Parque Nacional de Sete Cidades, the buffer area and plant resources; and elucidating aspects of the relationship between residents and PNSC employees and collaborators. To this end, a qualitative and quantitative approach was adopted in the survey of data with the 14 social actors or seven families, who totaled 100% of the heads of households with permanent residence in the Morada Nova and Palmeira da Emília communities. The initial socioeconomic profile of the communities was raised through semi-structured interviews. For the collection of ethnobotanical data, semi-structured interviews and Free List were carried out, associated with the complementary techniques of New Reading and Non-specific Induction. The plants mentioned were collected by Guided Tour. For the diagnosis of Environmental Perception, three types of data collection were applied: Semi-structured interviews, informal conversations and non-participant observation. The communities studied have a low level of education, low income and use a wide variety of plants, resulting in the survey of 34 botanical families associated with 11 utilitarian categories, with an emphasis on medicinal, food and construction uses. The ethnospecies with the highest use value were Anacardium occidentale L., Ximenia americana L., Terminalia fagifolia Mart. & Zucc. Ex Eichler, Parkia platycephala Benth. and Caryocar cuneatum Witm. respectively. There is a prevailing perception that the environment is important and 85,7% of the residents understand their role in conservation, suggesting viable actions to protect the flora, however, socio-environmental conflicts and feelings of estrangement on the part of the communities have been identified, highlighting the need for resumed in Environmental Education actions to spread the Park's role and strengthen the link between the UC and the surrounding communities. To this end, the following themes were suggested: 1. Man, nature and the environment; 2. Parque Nacional de Sete Cidades: What is it for and why was it created ?; 3. Utilitarianism and conservation; 4. Ecological activities at PNSC; 5. Mission of communities to the PNSC and 6. Useful exotic plants: Minimizing impacts on native flora.